Faktor-faktor yang Mempengaruhi Jumlah Pembelian Daging Sapi di Pasar Sentral Kota Makassar - Nanang Wirahady; Isra Azis G. (Jurnal Peternakan Lokal, 2021)
Beef is a high nutritional source of animal protein with an increasing demand. Several factors influence consumers in purchasing beef, namely the amount of purchase, purchase price, income, consuming experience, number of family dependents and education. These five factors are closely related to the amount of meat consumption by consumers in the Makassar Central Market. This research was conducted from June to August 2007 in the Central Market of Makassar City with 67 respondents. These five factors turned out to have an influence on the number of purchases where the results of the multiple linear regression showed a figure of 53.33 kg / month